Establishing relationship between characteristics of preventive maintenance and cost performance - Au-Yong, Cheong Peng; Ali, Azlan Shah; Ahmad, Faizah (2012)
The building maintenance costs are rising rapidly from time to time due to poor maintenance in the past. In UK, total spending on building maintenance had a dramatically increase of 66% in the past 10 years. In Malaysia, the development plan allocation for repair and maintenance works in building sector increased from RM296 million during the Eighth Malaysian Plan to RM1,079 million during the Ninth Malaysian Plan. However, the development plan allocation for repair and maintenance works in the Tenth Malaysian Plan has decreased to RM500 million. The decrease of resource allocation for building maintenance activities urges the professions to develop solutions on reducing the maintenance costs. Thus, it is vital to identify the cost characteristics of preventive maintenance, includes scheduled maintenance and condition-based maintenance through literature review. The characteristics of preventive maintenance always affect the maintenance cost performance. Therefore, relationship between characteristics of preventive maintenance and maintenance cost performance must be established to understand and take into consideration in the maintenance planning stage. At the end, the significant relationship will be able to help the industry practitioners in selecting appropriate maintenance strategy with optimal maintenance expenditure, yet improving the maintenance outcome.